Ronin - Frankenheimer, John 1930-2002.; De Niro, Robert; Mancuso, Frank; Reno, Jean 1948-.; McElhone, Natascha 1971-.; Skarsga& 778;rd, Stellan; Bean, Sean.; Pryce, Jonathan (United States United Artists Pictures, an FGM Entertainment Production, 1998)
A woman hires a team of masterless samurais known as Ronins to reclaim a mysterious suitcase. Conflicts arise when one Ronin betrays the team by swapping suitcases intending to fulfill his personal gains.
Producer : Frank Mancuso, Jr. ; Executive Producer : Paul Kelmenson ; Screenplay : J.D. Zeik and Richard Weisz ; Story : J.D. Zeik.
Cast : Robert De Niro, Jean Reno, Natascha McElhone, Stellan Skarsgard, Sean Bean, Skipp Sudduth, Michael Lonsdale, Jan Triska and Jonathan Pryce.
Keywords: Assassins -- Drama; Betrayal -- Drama; Treason -- Drama; Adventure films; Spy films